2015
DOI: 10.1155/2015/789027
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Remodelling Is Improved by 2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-glucoside Involving the Smad3 Pathway in Spontaneously Hypertensive Rats

Abstract: Hypertension is a common health problem that substantially increases the risk of cardiovascular disease. The condition increases blood pressure, which causes alterations in vascular structure and leads to the development of vascular pathologies. 2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-glucoside (THSG), a resveratrol analogue extracted from a Chinese medicinal plant, has been proven to have numerous vascular protection functions. This study investigated whether THSG can improve vascular remodeling, which has thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…THSG can inhibit TGF‐β protein expression in rat cardiac stem cells . THSG also inhibited the acetylation of SMAD3 and suppressed FN and COL1A2, COL3A1 expression in spontaneously hypertensive rats . Our current data had also supported the potential anti‐fibrotic activities of THSG.…”
Section: Discussionsupporting
confidence: 77%
“…THSG can inhibit TGF‐β protein expression in rat cardiac stem cells . THSG also inhibited the acetylation of SMAD3 and suppressed FN and COL1A2, COL3A1 expression in spontaneously hypertensive rats . Our current data had also supported the potential anti‐fibrotic activities of THSG.…”
Section: Discussionsupporting
confidence: 77%
“…Compared to WKY, SHR TA VSMCs showed a higher level of mRNA level of collagen types I and III, the two predominant isoforms of collagen in the aorta, which indicates an increase in collagen synthesis in VSMCs from stiffer aortas. The TIMP1/MMP ratio was also significantly increased in SHR TA VSMCs vs. WKY TA VSMCs, which were consistent with the previous observation of aortic tissues in SHRs (Duan et al., 2015). Since TIMP1 is a well‐recognized inhibitor of MMPs, which participate in collagen degradation (Duan et al., 2015), this increase in TIMP‐1 induced by SHR aortic VSMCs might contribute to the unfavorable collagen accumulation in the aortic wall (Zhou, Lee, Stoll, Ma, Wiener, et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The TIMP1/MMP ratio was also significantly increased in SHR TA VSMCs vs. WKY TA VSMCs, which were consistent with the previous observation of aortic tissues in SHRs (Duan et al., 2015). Since TIMP1 is a well‐recognized inhibitor of MMPs, which participate in collagen degradation (Duan et al., 2015), this increase in TIMP‐1 induced by SHR aortic VSMCs might contribute to the unfavorable collagen accumulation in the aortic wall (Zhou, Lee, Stoll, Ma, Wiener, et al 2017). In addition, using the 3D reconstituted model, we revealed that SHR TA VSMCs induced collagen disarray in both orientation and fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3,5, 4’-tetrahydroxystilbene-2-O- β -D-glycoside (TSG) is the main bioactive ingredient extracted from the traditional Chinese medicinal herb Polygonum multiflorum Thunb which has been used safely in China for approximately two millennia, and has been reported to have a wide spectrum of pharmacologic functions. TSG has been reported to help people live longer [18], protect impaired neural networks [19], improve blood flow [20], attenuate inflammatory responses [21], prevent the production of oxygen radicals and protect against oxidized LDL-induced endothelial dysfunction [22]. Previously, we demonstrated that TSG inhibits lysophosphatidylcholine (LPC)-induced apoptosis of human umbilical vein endothelial cells (HUVECs) by activating glutathione peroxidase and superoxide dismutase, clearing intracellular reactive oxygen species (ROS), and reducing lipid peroxidation [21, 23].…”
Section: Introductionmentioning
confidence: 99%